Developing occupational readiness among brain-injured educable mentally retarded (intermediate level) - Paqueo, Elisa Buniel 1943- (1973)
Borne out of the liberation theory of Jacques Maritain, the study attempted to bring into focus the meaningful interrelationship of the following factors: learning characteristics of brain-injured educable mentally retarded in the intermediate level, instructional millieu and goal to bring about a unified view of teaching pre-occupational skills to these children. The objectives of the study were approached through integrative reasearch. Literature in the field were reviewed. Findings pointed out to a direct teaching approach for the brain-injured mentally retarded. The researcher found out that there is a deficiency in input control among brain-injured educable mentally retarded and control of stimulus is of important concern for teachers.